Does Postsecondary Education Result in Civic Benefits?. (2nd November 2017) - Doyle, William R.; Skinner, Benjamin T.
ABSTRACT: Public support for higher education depends in part on the idea that additional postsecondary education results in civic benefits including voting, volunteering, and donating to non-profit causes. We expanded on the literature on civic benefits of higher education by utilizing a rich set of location-based instruments to identify the relationship between additional postsecondary education and civic behaviors. Using data from the National Longitudinal Survey of Youth 1997, we estimated the impact of postsecondary education on civic behaviors for a group of young people aged 29 to 33 years by 2013. These new estimates indicated that an additional year of higher education increased the probability of voting by 7.7% in the 2010 election. We also found statistically significant though substantively small impacts of postsecondary education on volunteerism and donations to nonprofits, with effect sizes of .1 for voluntarism and .13 for donations.